#### Answer

$R(x)$ = $(f\circ g\circ h)(x)$ for
$h(x)=\sqrt{x}, $
$g(x)=x-1$, and
$f(x)=\sqrt{x}$

#### Work Step by Step

$(f\circ g\circ h) (x)=f[g(h(x))]$
If we used a calculator, step by step,
for each step,
define the operation we would perform on the current result.
Starting with x, we would
1. calculate $\sqrt{x},\ \ \ h(x)=\sqrt{x}$
2. subtract 1 from the current result, $\ \ g(x)=x-1$
3. if the current result was R, calculate $\sqrt{R},\ \ \ f(x)=\sqrt{x}$
$R(x)$ = $(f\circ g\circ h)(x)$ for
$h(x)=\sqrt{x}, g(x)=x-1$, and $f(x)=\sqrt{x}$